Impact of Flood Mitigation Project on the River Water Salinity - Abdullah, Siti Nor Fazillah; Desa, Safari Mat; Awang, Suriyani; Sulaiman, Ahmad Husaini; Ismail, Azimah; Juahir, Hafizan; Jusoh, Azman Mat; Yahaya, Nasehir Khan E. M.; Hashim, Norbaya; San, Liew Yuk; Aminuddin, Normadihah M.; Hanapi, Nur Hanis Mohamad (Trends in Sciences, 2022)
The impact of flood mitigation project in the Kemaman River Basin was assessed in this study. Salinity intrusion was simulated in the study area by 1D numerical model. A 1-D hydrodynamic model coupled with a salinity model was used to analyze the salinity intrusion within Chukai River after the implementation of the flood mitigation project. The model was calibrated and validated using the data measured in Chukai River at 3 points from January 2007 until August 2013. Water quality simulation of salinity has been carried out once an excellent hydrodynamic model was established. The simulated river flow was reasonably matched to the measured data with R2 value 0.88, 0.92 and 0.82, respectively. Results suggest that after the realignment of Chukai River, the seawater intrudes further to the upstream river, causing the increasing salinity in the river about 10 - 15 ppt. However, with the floodway development, the channel would allow more water from Kemaman River being discharged into Chukai River. Increased in the volume of water in Chukai River has led to seawater dilution. Further, it invades the unique stretch of Chukai River and takes the salinity back to the initial state. Findings from the implementation of the flood mitigation project in the Kemaman river basin has benefitted the local society, watershed, and the surrounding biota ecosystems. Importantly, a greater prevention with the risk of repetitive flood damage to the buildings and structures in Kemaman area which has significantly achievable. HIGHLIGHTS Salinity model is used for flood mitigation project High salinity in Chukai river resulted from seawater intrusion Hydrodynamic model is to assess the water quality simulation